Tumor-associated macrophages: Prognostic and therapeutic targets for cancer in humans and dogs - Brady, Rachel V.; Thamm, Douglas H. (Frontiers in Immunology, 2023)
Macrophages are ancient, phagocytic immune cells thought to have their origins 500 million years ago in metazoan phylogeny. The understanding of macrophages has evolved to encompass their foundational roles in development, homeostasis, tissue repair, inflammation, and immunity. Notably, macrophages display high plasticity in response to environmental cues, capable of a strikingly wide variety of dynamic gene signatures and phenotypes. Macrophages are also involved in many pathological states including neural disease, asthma, liver disease, heart disease, cancer, and others. In cancer, most tumor-associated immune cells are macrophages, coined tumor-associated macrophages (TAMs). While some TAMs can display anti-tumor properties such as phagocytizing tumor cells and orchestrating an immune response, most macrophages in the tumor microenvironment are immunosuppressive and pro-tumorigenic. Macrophages have been implicated in all stages of cancer. Therefore, interest in manipulating macrophages as a therapeutic strategy against cancer developed as early as the 1970s. Companion dogs are a strong comparative immuno-oncology model for people due to documented similarities in the immune system and spontaneous cancers between the species. Data from clinical trials in humans and dogs can be leveraged to further scientific advancements that benefit both species. This review aims to provide a summary of the current state of knowledge on macrophages in general, and an in-depth review of macrophages as a therapeutic strategy against cancer in humans and companion dogs.